2007
DOI: 10.1007/s10461-007-9281-0
|View full text |Cite
|
Sign up to set email alerts
|

Barebacking among MSM Internet Users

Abstract: This theory-driven study explored the phenomenon barebacking among Men who have Sex with Men (MSM) Internet users. Two hundred and forty men were recruited online and asked to complete a web-based survey. Forty percent of men in this geographically diverse sample reported engaging in bareback sex. Consistent with other research, findings demonstrate that compared with non-barebackers, men who engage in bareback sex are more likely to use alcohol in sexual contexts, use the Internet to meet sex partners, engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 61 publications
(94 reference statements)
8
99
1
8
Order By: Relevance
“…The most common factor associated with drug use, however, is low self-esteem (e.g., Davis et al 2006;Green and Halkitis 2006;Grov 2010;Kelly et al 2009)-often shown to be associated with higher-than-normal levels of drug usage for gay men. Many studies also report that gay men who use crystal methamphetamine or other drugs are more likely to engage in risky sexual practices (i.e., bareback sex), which, in turn, could amplify the spread of HIV (Berg 2008;Davis et al 2006;Grov 2010Grov , 2012.…”
Section: Gay Men Drug Use and The Internetmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common factor associated with drug use, however, is low self-esteem (e.g., Davis et al 2006;Green and Halkitis 2006;Grov 2010;Kelly et al 2009)-often shown to be associated with higher-than-normal levels of drug usage for gay men. Many studies also report that gay men who use crystal methamphetamine or other drugs are more likely to engage in risky sexual practices (i.e., bareback sex), which, in turn, could amplify the spread of HIV (Berg 2008;Davis et al 2006;Grov 2010Grov , 2012.…”
Section: Gay Men Drug Use and The Internetmentioning
confidence: 99%
“…Gay drug usage also seems to be higher among those men who seek drugs and sex partners on the Internet compared with those who do not (e.g., McKirnan et al 2007); in fact, the virtual space of gay on-line "communities" is an important source for gay men seeking illicit drugs (e.g., Berg 2008;Carpiano et al 2011;Golub et al 2005;Green and Halkitis 2006;Grov 2010Grov , 2012. For example, one study of men at a gay pride festival in Atlanta, GA found that those men who met a sexual partner on the Internet reported higher levels of crystal usage (Benotsch et al 2002).…”
Section: Gay Men Drug Use and The Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with samples of mixed HIV-infected and uninfected MSM have found high rates of intentional unprotected anal intercourse, ranging from 14% to 46%. [2][3][4][5][6] Previous research has also shown HIVinfected MSM to be significantly more likely than HIV-uninfected MSM to report barebacking behavior. 5,6 In studies exclusively of HIV-infected MSM, the frequency of barebacking has been shown to be as high as 84%.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Among mixed serostatus samples, barebackers have been found to be more likely to use the Internet to meet sexual partners 2 and spent significantly more time on the Internet looking for sexual partners 3,4 ; reported significantly higher peer norms accepting unprotected sex 2 ; were more likely to use alcohol in sexual contexts 2 ; and were more likely to have reported engaging in both unprotected insertive and receptive anal sex. 2 Studies have also found evidence of strategic positioning (i.e., engaging in insertive rather than receptive sex) and serosorting (i.e., engaging in sex with individuals of the same known HIV serostatus) among MSM who report barebacking behavior. [3][4][5][6] Some researchers point to these findings as evidence of complex, harm-reduction decision-making informed by scientific evidence about the dynamics of HIV transmission and sexual risk among MSM.…”
Section: Introductionmentioning
confidence: 99%